PENGARUH UKURAN PERUSAHAAN DAN OPINI AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2018 - Rakhmi Ridhawati; M.Riduan Abdillah; Farida Ariyana (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract, This research aims to prove the effect of company size and audit opinion on audit delay in food and beverage companies listed on the Indonesia Stock Exchange in 2015-2018. This research method is a quantitative method. This research sample selection method using purposive sampling method. The dependent variable in this research is audit delay, while the independent variables in this research are company size and audit opinion. The population in this research were food and beverage companies listed on the Indonesia Stock Exchange during the 2015-2018 period, totaling 56 companies. The sample selection in this research using purposive sampling method. The research sample that was determined as many as 36 research samples. The analysis of this research uses multiple linear regression. The results showed that company size had no effect on audit delay, while audit opinion had an effect on audit delay.